Bledius hyalinus sp. nov. (Coleoptera: Staphylinidae: Oxytelinae), of the forcipatus group, first recorded from coastal Brazil - Bortoluzzi, Sidnei; Caron, Edilson (Zootaxa, 2019)
A new species group, forcipatus of Bledius, is reported from Coastal Brazil, extending its geographical range and increasing to seven the number of species. A new species, Bledius hyalinus Bortoluzzi & Caron is described, and the key to identification of Brazilian coastal Bledius is updated.